PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN DALAM PENCEGAHAN ULKUS DIABETIK PADA PASIEN DIABETES MELLITUS - Arvida. Bar; Devia Devia; Daryanto Daryanto; Yellyanda Yellyanda (NHM PRESS, 2021)
The purpose of this study was to determine the effect of health education on knowledge in the prevention of diabetic ulcers in patients with diabetes mellitus. Diabetes mellitus (DM) is a chronic disease characterized by blood glucose levels exceeding normal and disturbances of carbohydrate, fat and protein metabolism caused by a relative or absolute deficiency of the hormone insulin and if left uncontrolled, acute metabolic complications and long-term vascular complications can occur. , both microanglopathy and macroanglopathy. This study uses a Quasi Experimental approach with a pre and post test design. The sample in this study was 40 respondents with purposive sampling technique. This study took place at the Tanjung Pinang Health Center, Jambi City, using a questionnaire instrument as many as 10 questions and using leaflets. The test used is the Wilcoxon test. The results showed that the p-value (0.000) < 0.05 means that there is an effect on health education on knowledge in preventing diabetic ulcers. The level of knowledge of respondents before being given health education was 40 people who had a low level of knowledge. After being given health education, it showed a higher level, namely 3 low people and 37 respondents had good knowledge. The results of this study are expected to be a consideration or recommendation for the person in charge of the chronic disease program at the puskesmas should develop an appropriate program so that people with diabetes mellitus can have good knowledge about their disease so that they can carry out good self-management